Encapsulation Natural Oils Plant Based Using Freeze-Drying - Alyanis Mufid SWM; Soraya Ratnawulan Mita; Patihul Husni (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Natural oils, such as essential oils and oils with high unsaturated fatty acids, can be derived and extracted from plant sources. Essential oils contain aromatic compounds commonly used in the food industry, while oils rich in unsaturated fatty acids, such as omega-3, -6, and -9, along with vitamin E, are highly beneficial in industrial sectors. Furthermore, natural oils possess antimicrobial and antioxidant properties that are valuable in daily life. However, degradation of natural oils is inevitable due to various external factors such as temperature, humidity, and light. Therefore, an effective technique is required to enhance the stability of natural oils, with one of the methods being freeze drying, using wall materials made from various polymers depending on the intended application. This review aims to summarize the development of natural oils encapsulated by freeze dryingThe literature search in this review was conducted using the search engines Google Scholar and ScienceDirect. The selected papers used for this review consist of original research articles published between 2021 and 2025, focusing on natural oils unsaturated fatty acids or essential oils as the primary subject of study. Stability can be improved by examining thermal analysis parameters in various natural oils, such as walnut, sacha inchi, rose damascena, mandarin, and boswellia sacra. Storage at low temperatures helps enhance the chemical stability of natural oils. In natural oils, both essential oils and oils with high unsaturated fatty acids, stability improvement can be achieved through freeze drying using polymers as wall materials such as polysaccharides, proteins, gums, lignin, or other polymers. The use of proper machine freeze drying parameter settings is also necessary to obtain the best results with high encapsulation efficiency Keywords: Encapsulation, Essential Oils, Freeze Drying, Natural Product, Unsaturated fatty Acids.